2020
DOI: 10.1158/1078-0432.ccr-19-3354
|View full text |Cite
|
Sign up to set email alerts
|

CUE-101, a Novel E7-pHLA-IL2-Fc Fusion Protein, Enhances Tumor Antigen-Specific T-Cell Activation for the Treatment of HPV16-Driven Malignancies

Abstract: Purpose: To assess the potential for CUE-101, a novel therapeutic fusion protein, to selectively activate and expand HPV16 E7 11-20-specific CD8 þ T cells as an off-the shelf therapy for the treatment of HPV16-driven tumors, including head and neck squamous cell carcinoma (HNSCC), cervical, and anal cancers. Experimental Design: CUE-101 is an Fc fusion protein composed of a human leukocyte antigen (HLA) complex, an HPV16 E7 peptide epitope, reduced affinity human IL2 molecules, and an effector attenuated human… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…We have described two modular immunotherapeutics platforms, Immuno-STAT and Neo-STAT, for the co-presentation of defined peptide-HLA (pHLA) and co-modulatory ligands to AgS T cells, and engineered an affinity-attenuated variant of IL-2, IL2.FH, for use thereon. IL2.FH-bearing constructs, including an HPV-specific clinical candidate, CUE-101 (NCT03978689), are associated with 110-fold and 3.1-fold decreases in binding to IL2Rα and IL2Rβ, respectively, with minimal Treg and non-AgS T cell responses in vitro and in vivo 14 . While greater AgS selectivity was anticipated for LCMV-IST-IL2.FH 4 over LCMV-IST-IL2 2 due to attenuation of IL-2:IL-2R versus pHLA:TCR binding, this trend was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have described two modular immunotherapeutics platforms, Immuno-STAT and Neo-STAT, for the co-presentation of defined peptide-HLA (pHLA) and co-modulatory ligands to AgS T cells, and engineered an affinity-attenuated variant of IL-2, IL2.FH, for use thereon. IL2.FH-bearing constructs, including an HPV-specific clinical candidate, CUE-101 (NCT03978689), are associated with 110-fold and 3.1-fold decreases in binding to IL2Rα and IL2Rβ, respectively, with minimal Treg and non-AgS T cell responses in vitro and in vivo 14 . While greater AgS selectivity was anticipated for LCMV-IST-IL2.FH 4 over LCMV-IST-IL2 2 due to attenuation of IL-2:IL-2R versus pHLA:TCR binding, this trend was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-A*0201, HLA-A*1101 and HLA-A*2402, surveyed here in the context of Immuno-STAT, are collectively expressed by over half the global population and Neo-STAT extends potential pHLAs to include post-translational modifications and low affinity peptides 24 . In preclinical murine studies, CUE-101 and mCUE-101 elicit AgS T cell responses from both naïve and antigen-experienced precursors, with responses to mCUE-101 detectable in blood, spleen, and tumors, suggesting the potential to both invigorate T cell responses within tumors and initiate responses outside of immunosuppressive tumor microenvironments, which are relatively resistant to exhaustion 14 , 25 . Compelling applications of these platforms include enhancing T cell responses against essential antigens in cancer or infectious disease, especially where relevant AgS T cells are limiting or dysfunctional, and more efficiently activating or maintaining ACT cells ex/in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent report demonstrated that the same synTac scaffold used to image the HPV E7-specific T cells could selectively deliver covalently linked IL-2 (termed ImmunoSTAT) and expand E7-specific CD8 T cells, with antitumor efficacy in the HPV-driven TC-1 tumor model. 38 These capabilities will be expanded for imaging of CD4 T cells by generating synTacs containing class II pMHCs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies showed that CUE‐101 selectively binds to HPV‐specific CD8 + T cells and induces effector function in a dose‐dependent manner. In animal studies, CUE‐101 monotherapy, and combination therapy with an anti‐PD‐1 agent, induced selective expansion of HPV‐E7–specific CD8 + T cells, inhibited tumor growth, and improved survival 85 . CUE‐101 is being tested as a monotherapy in a phase 1 trial in HLA‐A02 patients with HPV‐16 + recurrent or metastatic HNSCC.…”
Section: Activating T Cells With Immuno‐statsmentioning
confidence: 99%